Average compositions of serpentine and fuchsite from hole BT1B, Oman Drilling Project - Andreas Beinlich; Oliver Plümper; Esmée Boter; Inigo A Müller; Fatma Kourim; Martin Ziegler; Yumiko Harigane; Peter B Kelemen; The Oman Drilling Project Phase 1 Science Team (PANGAEA, 2020)
The presented serpentine and fuchsite (Cr-muscovite) data were derived from representative carbonate-bearing serpentinite and listvenite samples from Hole BT1B, OmanDP. Electron microprobe analysis was conducted using the JEOL 8530F FE electron microprobe at Centre for Microscopy, Characterization and Analysis (CMCA), The University of Western Australia, using an acceleration voltage of 15 keV and a fully focused beam. The general analytical procedure and application of reference materials follow the method described in Beinlich et al. (2018; doi:10.1038/s41467-018-03039-9).